2016
DOI: 10.17795/ijcp-3998
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Prevalence Rate and the Prognostic Effect of Human Papilloma Virus Infection in a Group of Patients With Oral Cavity Squamous Cell Carcinoma

Abstract: BackgroundSquamous cell carcinoma (SCC) is the most common malignancy of the oral cavity. A relationship between the human papilloma virus (HPV) infection and the prognosis of oral cavity SCC (OCSCC) has been discussed before.ObjectivesWe investigated the prevalence rate of HPV status in patients with OCSCC, and its effects on clinicopathological characteristics of tumors and patients’ prognosis.Patients and MethodsSections of formalin-fixed, paraffin-embedded tissue blocks from 114 histopathologically confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 48 publications
(100 reference statements)
4
13
0
Order By: Relevance
“…However, our current findings suggest that patients with HPV 16-associated OCSCC had worse 5-year LR rates following standard treatment compared to those without HPV 16 infections. Consistent with our data, recent studies show that patients with HPV-positive OCSCC had worse survival ( n : 300–1002) than those with HPV-negative OCSCC in India [ 39 ], Iran [ 40 ], Croatia [ 41 ], and Taiwan [ 5 , 9– 11 , 42 ]. Consequently, our data should caution against the reliance on radiotherapy alone as a general treatment strategy for patients with HPV-positive OCSCC.…”
Section: Discussionsupporting
confidence: 92%
“…However, our current findings suggest that patients with HPV 16-associated OCSCC had worse 5-year LR rates following standard treatment compared to those without HPV 16 infections. Consistent with our data, recent studies show that patients with HPV-positive OCSCC had worse survival ( n : 300–1002) than those with HPV-negative OCSCC in India [ 39 ], Iran [ 40 ], Croatia [ 41 ], and Taiwan [ 5 , 9– 11 , 42 ]. Consequently, our data should caution against the reliance on radiotherapy alone as a general treatment strategy for patients with HPV-positive OCSCC.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, there was a significant association between HPV positivity and the grade of the primary tumor (30,31). Interestingly, these studies could not find a significant correlation between HPV positivity and other prognostic markers, such as perivascular or perineural invasion, while associated with the overall survival rate (15,23,29).…”
Section: Discussionmentioning
confidence: 85%
“…Although a better survival rate in HPV positive HNSCC was reported by a couple of previous studies ( 15 ), the majority of studies, which investigated the prognostic role of HPV positivity in HNSCC patients, found it highly correlated with poor tumor-cell differentiation, which may act as a prognostic marker and play a vital role in the pathways that enhance lymphatic metastasis ( 28 , 29 ). A similar result was also reported in Iran with a higher mortality rate in HPV positive HNSCC ( 15 ). In addition, there was a significant association between HPV positivity and the grade of the primary tumor ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…To date, studies seeking potential predictive molecular markers for OSCC have been extensively performed and some markers were identified as significantly correlating with tumor biological response and clinical features in vitro and in vivo [ 28 32 ]. Some molecular markers are even enable to significantly influence survival [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%